2011
DOI: 10.1007/s10811-011-9771-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for a low-cost Haematococcus pluvialis medium reveals an unexpected impact of a low N/P ratio on vegetative growth

Abstract: Haematococcus pluvialis is the current better source of natural astaxanthin, a high-value carotenoid. Traditionally, the production process of astaxanthin by this algae is achieved by a two-stage system: during the first stage, vegetative "green" cells are produced and then converted, in the second stage, into cysts that accumulate astaxanthin. In this work, a medium screening strategy based on the mixing of a 3-component hydroponic fertilizer was applied to identify a new formulation optimized for the vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 32 publications
2
22
1
6
Order By: Relevance
“…This was taken as a indicator for the absence of nutrient limitation. FloraMicro and FloraGro composition can be found in Tocquin et al (2012). In one culture, pH of the medium was stabilized to a value close to 7.5 by injecting pure CO 2 while in the other, pH was not stabilized.…”
Section: Methodsmentioning
confidence: 99%
“…This was taken as a indicator for the absence of nutrient limitation. FloraMicro and FloraGro composition can be found in Tocquin et al (2012). In one culture, pH of the medium was stabilized to a value close to 7.5 by injecting pure CO 2 while in the other, pH was not stabilized.…”
Section: Methodsmentioning
confidence: 99%
“…However, nitrogen is an essential element for microalgae's growth development, reproduction and other physiological activities (Wang et al, 2013). Ammonium is not only the most preferred nitrogen source for algae, but also the most energetically efficient source, since less energy is required for its uptake (Tocquin et al, 2012). Current results showed that alternative media (NPK and M+NPK) had high nitrogen and phosphorus contents, indicating that they were good tools when only nutrients were needed.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, current results indicated that high phosphate (2.8 mg.L -1 ) was the key feature leading to beneficial effects on cell growth. Compared to nitrate, phosphate received less attention in optimization approaches although it promoted growth at moderate and low concentrations (Tocquin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Az asztaxantin védelmet nyújt az UV károsító hatásával szemben, valamint jelentős gyulladáscsökkentő, ill. immunerősítő hatása van (KOBAYASHI & OKADA 2000). Ez utóbbi magyarázza a széleskörű felhasználási lehetőségeit a humánegészségügy területén is (LORENZ & CYSEWSKI 2000, FÁBREGAS et al 2001, DOMÍNGUEZ-BOCANEGRA et al 2007, CHOI et al 2011, TOCQUIN et al 2012. Az állati takarmányozásban pedig elsődlegesen mint színezőanyagot használják (pl.…”
Section: áBra B)unclassified